Suppression of texture formation in metals being electrodeposited at the force influence opposite to the texture axis - Гирин, Олег Борисович (Eastern-European Journal of Enterprise Technologies, 2013)
The aim of the work was the experimental verification of the validity of the phenomenon of phase formation through a stage of liquid state in metallic materials being electrodeposited. For that the features of formation of crystallographic texture in metals (copper and nickel) being electrodeposited under the influence of centrifugal force in the direction opposite to the texture axis was investigated. The value of overload was varied stepwise from 1g to 1256g. Quantitative estimation of the degree of texturing of electrodeposited metals shows that the increase of overload at the influence of centrifugal force in the direction opposite to the texture axis causes the growth of the degree of dispersion of the axial orientations with the axes [210] and [221] in nickel deposits and with the axis [110] in copper deposits. At that, even minor overload (35g) in the direction opposite to the texture axis causes significant disordering in preferred orientation of crystal lattices of metal grains. The effect of suppression of the process of texture formation in metals being electrodeposited up to the complete disordering of crystal lattices of grains under the influence of centrifugal force in the direction opposite to the texture axis was found. The obtained result proves the validity of the phenomenon of phase formation through a stage of liquid state in metallic materials being electrodeposited.